In the realm of Nachan Kan: Postclassic Maya archaeology at Laguna de On, Belize - Masson, Marilyn A., author; University Press of Colorado, publisher (Colorado State University. Libraries, 2000)
The prevailing view of the lowland Maya during the Postclassic period (A.D. 1050-1500) has been one of an impoverished, degenerated" society devoid of cultural accomplishment. However, Marilyn A. Masson offers a fresh interpretation of this society as one that represented a complex, sophisticated, extensive organization of semiautonomous units that were closely integrated, yet embraced a decentralized political economy. In the Realm of Nachan Kan opens a window of Postclassic Maya patterns of cultural development and organization through a close examination of the small rural island of Laguna de On, a location that was distant from the governing political centers of the day. Using diachronic analysis of regional settlement patterns, ceramic traditions, household and ritual features, and artifacts from the site, Masson tracks developmental changes throughout the Postclassical period. These data suggest that affluent patterns of economic production and local and long-distance exchange were established within northern Belize by the eleventh century, and continued to develop, virtually uninterrupted, until the time of Spanish arrival. In addition, Masson analyzes contemporary political and religious artistic traditions at the temples of Mayapan, Tulum, and Santa Rita to provide a regional context for the changes in community patterns at Laguna de On. These cultural changes, she maintains, are closely correlated with the rise of Mayapan to power and participation of sites like Laguna de On in pan-lowland economic and ritual interaction sphere. Offering a thoroughly new interpretation of Postclassic Mayan civilization, In the Realm of Nacham Kan is a must for scholars of Mesoamerican history and culture.--Book jacket.
1. Introduction: From the Eleventh Century Forward -- 2. The Physical and Political Geography of Laguna de On -- 3. Northern Belize Postclassic Ceramic Chronology -- 4. Community Patterns at Laguna de On -- 5. Economic Production and Exchange at Laguna de On -- 6. Religious institutions and Elite Power at Postclassic Maya Communities -- 7. Postclassic Maya Cultural Development in the Realm of Nachan Kan -- Appendix: A Comparison of Hocaba and Tases Ceramic -- Complexes at Mayapan.
Keywords: Laguna de On Site (Belize); Mayas -- Belize -- Orange Walk District -- Antiquities; Maya pottery -- Belize -- Orange Walk District; Mayas -- Mexico -- Chetumal (Province) -- Kings and rulers; Land settlement patterns -- Belize -- Orange Walk District; Orange Walk District (Belize) -- Antiquities